2017
DOI: 10.1108/lm-02-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Linking exploration to academic performance

Abstract: Purpose Substantial empirical research has addressed the antecedents of students’ academic performance. Building on these insights, the purpose of this paper is to extend the related literature by investigating the impact of students’ exploration on their academic performance. Furthermore, to provide a better understanding of this relationship the authors incorporate two sequential mediators, namely, information seeking and academic self-efficacy. Design/methodology/approach Quantitative approach using self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The search process encompasses not only the action of seeking and using sources, but also the development of thoughts about a topic and the feelings that typically accompany such evolution of thinking (Kuhlthau 1988). This is aligned with a study done by Gkorezis, Kostagiolas and Niakas (2017) who supported information seeking as a sequence of actions to satisfy the various essential needs such as affective, cognitive and physiological, that are generated based on the demands created within a set of contexts such as individual, work-life, socio-cultural and politico-economic environment. According to Myrick (2017) the process of information seeking involves a mixture of affective, physical and cognitive human experience, while emotions play a vital role in the information retrieval process.…”
Section: Introductionsupporting
confidence: 53%
“…The search process encompasses not only the action of seeking and using sources, but also the development of thoughts about a topic and the feelings that typically accompany such evolution of thinking (Kuhlthau 1988). This is aligned with a study done by Gkorezis, Kostagiolas and Niakas (2017) who supported information seeking as a sequence of actions to satisfy the various essential needs such as affective, cognitive and physiological, that are generated based on the demands created within a set of contexts such as individual, work-life, socio-cultural and politico-economic environment. According to Myrick (2017) the process of information seeking involves a mixture of affective, physical and cognitive human experience, while emotions play a vital role in the information retrieval process.…”
Section: Introductionsupporting
confidence: 53%
“…Different studies investigated the effects of informationseeking behavior, IT skills, reading/writing ability, and resilience on the academic performance of students individually. For example, the positive relationship between exploration and academic performance is mediated by information-seeking, which in turn is mediated by academic self-efficacy (Gkorezis et al, 2017). Similarly, in the context of digital literacy, the study found that technology indirectly influences academic performance through self-directed learning (Rashid and Asghar, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 81%
“…It is anticipated that these variables will influence the academic performance of students. Recent research, for example, found that information seeking, and therefore academic selfefficacy, mediates the positive relationship between exploration and academic performance (Gkorezis et al, 2017). A recent study found a connection between ICT adoption and academic performance in a conservative setting (Basri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%